Severe Extra-Cerebral Anticoagulant-Related Bleeding in Intensive Care Unit: A Retrospective Study From 2000 to 2013. Issue 47 (November 2015) - Hauguel, M; Boelle, Py; Pichereau, C; Bourcier, S; Bigé, N; Baudel, JL; Maury, E; Guidet, B; Ait-Oufella, H
Abstract : Abstract: Bleeding is the most frequent complication of anticoagulant therapy, responsible for a number of hospitalizations or deaths. However, studies describing the management and prognosis factors of extra-cerebral anticoagulant-related bleedings in intensive care unit (ICU) are lacking. Retrospective observational study in an 18-bed ICU in a tertiary teaching hospital. From January 2000 to December 2013, all consecutive patients, older than 18 years, admitted for severe anticoagulant-related bleeding (SAB) except intracerebral site were included. A total of 100 patients were included, the mean age was 77 ± 11 years and 62% were women. SAB incidence in ICU doubled over 10 years ( P = 0.03). In ICU, the average length of stay was 5 ± 6 days and mortality was 30%. Nonsurviving patients had a higher SAPS II (78 ± 24 vs 53 ± 24, P < 0.0001), a higher SOFA (9.0 ± 3.6 vs 4.7 ± 3.4, P < 0.0001) and received more frequently support therapy such as mechanical ventilation (87% vs 16%, P < 0.0001) and vasopressors (90% vs 27%, P < 0.0001). The volume of blood-derived products transfused was more important in nonsurvivors mainly during the first 24 hours of resuscitation. Rapid anticoagulant reversal therapy was associated with better prognosis (ICU survivors 66% vs 39%, Fisher test P = 0.04). Anterior abdominal wall was identified as a frequent site of bleeding (22%) due to epigastric artery injury during subcutaneous injection of heparin and was associated with a large mortality (55%). Extra-cerebral SAB is a life-threatening complication that requires rapid resuscitation and anticoagulant reversal therapy. Injection of heparin should be done carefully in the subcutaneous tissue thereby avoiding artery injury.